Critical Success Factors of Technology-based Start-ups in the UAE: The Moderating Role of the Organizational Life Cycle - ALNUAIMI, MANSOOR ALKAITOOB (2025)
This study examines the Critical Success Factors (CSFs) influencing the performance and sustainability of Technology-based Start-ups (TBS) in the United Arab Emirates (UAE), while examining the moderating effect of the Organizational Life Cycle (OLC). Despite their potential for innovation and economic growth, TBS in the UAE, like elsewhere, suffer from high mortality rates, particularly in their early stages. This research identifies a broad set of CSFs categorized under entrepreneurial, intra-organizational, and inter-organizational attributes. Using a quantitative methodology grounded in the positivist paradigm, data was collected via an online survey targeting founders, CEOs, and other key leaders of TBS across the UAE. Multivariate statistical techniques, including factor analysis, cluster analysis, and multiple regression analysis, were applied to examine the relationships between CSFs and TBS success across different OLC stages. The findings demonstrate that the relevance and impact of specific CSFs vary significantly depending on the developmental stage of the startup. This research contributes to the existing literature by offering a stage-based classification of CSFs and highlights how the strategic alignment of resources at each stage of development enhances the likelihood of startup success. Additionally, the study provides valuable insights for policymakers, venture capitalists, and entrepreneurs by offering practical recommendations to support TBS at different lifecycle stages. Ultimately, the study reinforces the need for a context-specific approach to fostering startup ecosystems, particularly in emerging markets like the UAE.